Relationships between preference, rumen degradability, gas production and chemical composition of browses - Kaitho, R.J.; Nsahlai, I.V.; Williams, B.A.; Umunna, N.N.; Tamminga, S.; Bruchem, J. van (Springer, 1997)
The aim of this work was to assess whether degradability, gas production or chemical constituents could predict the preference of browses. Forty tropical browse species leaves with a crude protein (CP) content ranging from 79 to 307 g kg-1 DM were used for this study. The neutral detergent fibre (NDF) ranged from 220 to 694 g kg-1 DM, while acid detergent fibre (ADF) ranged from 146 to 523 g kg-1 DM. The NDF-bound nitrogen (NDFN) and ADF-bound nitrogen were particularly high in Calliandra calothyrsus, Acacia polyacantha, Sesbania sesban, Acacia venosa and Acacia hockii. High levels of tannins were observed in Acacia species especially A. dolichocephala, A. hockii, A. microbotrya and A. salicina. High levels were also observed in Flemingia macrophyla and Leucaena pallida. The browse species differed (P<0.05) in DM in sacco degradability coefficients. High potential degradability (PD) and effective degradability (ED) were observed in Sesbania spp, Moringa stenopetala, Indigofera arrecta, Chamaecytisus palmensis and Atriplex spThe browses differed (P<0.05) in asymptotic gas (Ag) production (m1 g-1 OM), but had similar (P>0.05) times of incubation at which half of the asymptotic gas had been formed. Preference and DM intake were positively correlated (P<0.01) to NDFN, but negatively correlated (P<0.05) to NDF and ADF. The PD and Ag were negatively (P<0.001) related to NDF, ADF and lignin. Total phenols (TP) and condensed tannins (CT) were negatively (P<0.05) related to PD, ED and Ag. A positive correlation was observed between CT and NDF-bound condensed tannins (r=0.55, P<0.001) and , CT and TP (r=0.40, P<0.01). Predicition equations were poor for DM intake and preference, moderate for gas production and good for potential and effective degradabilities. The phenolic components were more related to dry matter degradation and gas production than to preference and dry matter intake. NDFN and Ag made a positive contribution to both preference and DM intake. It was concluded that chemical constitutes such as N, NDF, NDFN, ADF and lignin are essential to predict the nutritive value of browses.